The impact of the task environment on strategic planning: an applied study in hotel organizations in the city of Karbala - علي عبد الحسين الجشعمي (Iraqi Journal for Administrative Sciences, 2024)
The purpose of this research is know and analyze of the elements and stages of the task environment, strategic planning in a sample of hotel organizations in Karbala. Researcher used the standards which are ready to identify the elements of the task environment and the stages of strategic planning. Data were analyzed by using a range of methods and means of statistical descriptive and analytical. One of the most important research results, the level of the elements of the task environment for most of the research sample was medium, and high-level stages of strategic planning for the middle of prescriptive, as well as a statistically significant effect between the elements of the task environment and the stages of strategic planning. Recommends the need to search hotel organizations interesting study and analyze the most influential elements of the environment in their organizations, as well as the adoption of scientific methods and technical phases of the correct application of strategic planning.